2002
DOI: 10.1111/1467-9450.00290
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of picture naming times in Icelandic

Abstract: Numerous studies have found that word frequency has a significant effect on the time it takes to name an object or read a word. Recently, claims have been made that this frequency effect is perhaps more correctly interpreted as an age of acquisition effect. This paper reports an experiment in which naming times in Icelandic for 175 stimuli from the Snodgrass and Vanderwart picture set were determined. A multiple regression analysis of naming times against a number of independent factors showed that objective a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
28
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 37 publications
2
28
0
2
Order By: Relevance
“…Results from both experiments show clearly that name agreement, rated familiarity, and AoA have the greatest impact on timed picture naming in Putonghua. Our results are compatible with studies in American English (Snodgrass & Yuditsky, 1996), British English (Ellis & Morrison, 1998), Dutch (Severens et al, 2005), French (Alario et al, 2004), Icelandic (Pind & Tryggvadottir, 2002), Italian (Dell'Acqua et al, 2000), and Spanish (Cuetos et al, 1999). Indeed, AoA and name agreement have significant independent effects on picture naming latency in every language studied, and all studies that include these variables report significant effects on picture naming latency (this was noted by Alario et al, 2004).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Results from both experiments show clearly that name agreement, rated familiarity, and AoA have the greatest impact on timed picture naming in Putonghua. Our results are compatible with studies in American English (Snodgrass & Yuditsky, 1996), British English (Ellis & Morrison, 1998), Dutch (Severens et al, 2005), French (Alario et al, 2004), Icelandic (Pind & Tryggvadottir, 2002), Italian (Dell'Acqua et al, 2000), and Spanish (Cuetos et al, 1999). Indeed, AoA and name agreement have significant independent effects on picture naming latency in every language studied, and all studies that include these variables report significant effects on picture naming latency (this was noted by Alario et al, 2004).…”
Section: Discussionsupporting
confidence: 93%
“…This is an estimate of the age at which the name of an object is learned, measured with subjective or objective values. Many studies report effects of subjective AoA on picture naming using retrospective adult rated estimates (Carroll & White, 1973;Gilhooly & Gilhooly, 1979;Morrison, Ellis, & Quinlan, 1992) and some studies also report effects of objective AoA-based on children's naming performance-on picture naming (Pind & Tryggvadottir, 2002). Morrison, Chappell, and Ellis (1997) observed a high correlation between rated and objective measures of AoA, and Ellis and Morrison (1998) found that both measures predict adult naming in their own study and in data published by Barry et al (1997) and Snodgrass and Yuditsky (1996).…”
mentioning
confidence: 98%
See 3 more Smart Citations